Dukungan Sosial Suami Terhadap Pemberian ASI Eksklusif di Wilayah Puskesmas Sinorang Kabupaten Banggai - Kasio, Yarike; Gunarmi, Gunarmi; Pramana, Cipta (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2024)
Background: Exclusive breastfeeding is one of the world's efforts to prepare healthy future generations from an early age.Objective: This research is to determine the relationship between husband's social support and exclusive breastfeeding for breastfeeding mothers at the Sinorang Community Health Center, Banggai Regency.Method: This research is quantitative research with a cross-sectional approach. Data analysis used in this research used the chi square test.Results and Discussion: There is a significant relationship (p value = 0.000) of husband's informative support with exclusive breastfeeding; there is a significant relationship (p value = 0.047) of husband's emotional support with exclusive breastfeeding; there is a significant relationship (p value = 0.000) of husband's instrumental support with exclusive breastfeeding; There is a significant relationship (p value = 0.024) of husband's appraisal support with exclusive breastfeeding.Conclusion: There is a relationship between social support consisting of informative support, emotional support, instrumental support, appraisal support and exclusive breastfeeding.